Mutagenesis in aromatic rice: current progress, challenges and future prospects - Hasibuzzaman, A S M; Perves, M; Chowdhory, M; Hasan, R; Begum, S N (Bangladesh Journal of Nuclear Agriculture, 2025)
Aromatic rice, renowned for its unique aroma and higher market value, is of considerable significance in global rice production. Mutation has become potent methods for strengthening agronomic features, increasing stress tolerance, and expanding the genetic diversity of crop plants. This review highlights the advancements in mutagenesis research focused on aromatic rice, emphasizing successful implementations in enhancing yield, fragrance, grain quality, and resilience to problematic conditions. Advanced mutation techniques, including gamma irradiation, EMS treatment, and the incorporation of genomic tools, have significantly expedited the induction and to characterize mutants. Notwithstanding these gains, obstacles, including restricted genetic diversity, difficulties in trait stabilization, and inadequate high-throughput screening methodologies. Furthermore, the integration of mutagenesis with contemporary genomics, transcriptomics, and genome editing techniques is yet inadequately investigated in the enhancement of aromatic rice. This review also observes advanced opportunities, such as TILLING platforms and CRISPR-based reverse genetics, to utilize mutagenesis with more efficiently and precisely. A thorough comprehension of induced genetic diversity and the functional validation of responsible genes will be vital for future breeding program. Mutagenesis continues to be a potential approach for creating enhanced fragrant rice varieties to satisfy the requirements of quality-focused markets and sustainable agriculture. Bangladesh J. Nuclear Agric., 39(1): 13-30, 2025